Applying Nanotechnology to Human Health: Revolution in Biomedical Sciences. (1st September 2009) - Shrivastava, Siddhartha; Dash, Debabrata
Abstract : Recent research on biosystems at the nanoscale has created one of the most dynamic science and technology domains at the confluence of physical sciences, molecular engineering, biology, biotechnology, and medicine. This domain includes better understanding of living and thinking systems, revolutionary biotechnology processes, synthesis of new drugs and their targeted delivery, regenerative medicine, neuromorphic engineering, and developing a sustainable environment. Nanobiosystems research is a priority in many countries and its relevance within nanotechnology is expected to increase in the future. The realisation that the nanoscale has certain properties needed to solve important medical challenges and cater to unmet medical needs is driving nanomedical research. The present review explores the significance of nanoscience and latest nanotechnologies for human health. Addressing the associated opportunities, the review also suggests how to manage far-reaching developments in these areas.